For love of money - malicious hacking takes an ominous turn. - Aaronson, L. (IEEE spectrum)
This paper discusses how programmers use the targeted Trojan horse attack to steal valuable confidential information via an email with a subject line or message containing language calculated to lure a particular recipient into opening the attachment. Because many antivirus programs recognize only threats that security experts have already seen and defined, unique Trojans go undetected as they enter a system. To detect a Trojan lurking on a hard drive, it helps to make sure that firewalls are optimally configured. Methods that identify Trojans by tell-tale file modifications and other suspicious behavior are already being developed. In the meantime, companies have recoursed to using proxy servers. Users are advised to regularly install software patches, avoid keeping valuable information on Internet-connected machines, and steer clear of unsolicited attachments, links and even disks and CDs.